Application of Assessment in Online Islamic Education Subjects - Dina Aulia Mildasari; Nur Ali; Mokhammad Yahya (Proceeding International Conference on Religion, Science and Education, 2023)
Distance learning began to be applied to prevent the spread of the Covid-19 outbreak, particularly in the school environment. There are still few educational institutions in Indonesia that prepare online mode as a normal part of learning. The majority of educational institutions in Indonesia convert face-to-face learning into distance learning by necessity due to the Covid-19 pandemic. Some changes in learning assessment activities such as the form of evaluation activities, evaluation instruments, and the form of evaluation reports, have been changed to reflect current learning situations. The objectives of this study include to find out: 1) Assessment planning; 2) Assessment activities; 3) Problems of Assessment in Islamic Education online at State Senior High School 1 and State Senior High School 8 Malang?. This research employs a descriptive qualitative research method. Qualitative research, research that emphasizes the aspect of in-depth understanding of a problem in addition to looking at problem for generalization research. The data collection techniques used were interviews, observations, and documentation. Data analysis consist of three streams of activities that occur simultaneously such as data reduction, data presentation, conclusion withdrawal, and verification. Efforts to check the validity of the data using triangulation techniques, such as comparing the results of the research obtained, as well as persistence of observation. Based on the results of research conducted in the field, it shows that: First, planning for the assessment of learning outcomes, namely: 1) Determining KKM (the Minimum Completion Criteria) for Islamic Education subjects; 2) Reviewing the syllabus and making lesson plans; 3) Analysing KI (the Core Competence) – KD (the Basic Competence) and determining assessment instruments. Second, assessment activities include cognitive, affective, and psychomotor assessments with diverse instruments. Third, there is the issues of assement the outcomes of Islamic Education online learning, which includes, among other things: 1) Network and supporting device availability; 2) Learning Lost; 3) Teacher innovation regarding online assessment.